The estimates spawning potential ratio of three dominant demersal fish species landed in Tegal, north coast of Central Java, Indonesia - DUTO NUGROHO; MUFTI P. PATRIA; JATNA SUPRIATNA; LUKY ADRIANTO (Biodiversitas Journal of Biological Diversity, 2017)
Nugroho D, Patria MP, Supriatna J, Adrianto L. 2017. The estimates spawning potential ratio of three dominant demersal fish species landed in Tegal, north coast of Central Java, Indonesia. Biodiversitas 18: 844-849. Java Sea is one of the important marine waters for fisheries purpose in Indonesia. The rich diversity of marine fish has been exploited for decades. Among them, demersal fish resource was commercially targeted by coastal fishers. The sustainability of demersal fishery is a crucial concern given the substantial economic contribution and its significant dependence of small-scale fishers for their livelihoods. The fishing intensity is considerable growing and tends to become threats their habitats. Three dominant species (Priacanthus tayenus, Scolopsis taeniopterus and Upeneus sulphureus) were selected in this study. To evaluate the vulnerability of these species to their bio-exploitation level, the spawning potential ratio (SPR) approach were applied. The calculation based on estimated length of first capture (Lc) indicates that SPR those demersal species occurred at less than 20%. These values indicate that existing fishery can be categorized as nearly fully exploited. Across broad range of species, 40% SPR is generally accepted as a proxy for Maximum Sustainable Yield (MSY) for recruitment overfishing in less resilience fish population.